If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6p + -3 = -12 + -5p Reorder the terms: -3 + -6p = -12 + -5p Solving -3 + -6p = -12 + -5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '5p' to each side of the equation. -3 + -6p + 5p = -12 + -5p + 5p Combine like terms: -6p + 5p = -1p -3 + -1p = -12 + -5p + 5p Combine like terms: -5p + 5p = 0 -3 + -1p = -12 + 0 -3 + -1p = -12 Add '3' to each side of the equation. -3 + 3 + -1p = -12 + 3 Combine like terms: -3 + 3 = 0 0 + -1p = -12 + 3 -1p = -12 + 3 Combine like terms: -12 + 3 = -9 -1p = -9 Divide each side by '-1'. p = 9 Simplifying p = 9
| (6-4)(8b^2-5b+6)= | | 13-[5+5y-3(y+3)]=-3(4y-7)-[8(y-1)-16y+18] | | 2(b+8)-9=18 | | 3=y-21 | | 8x-3=2x+33 | | 4x=4m | | (2x+y+1)(2x+y+1)= | | -5n=13-3+1n-2,2,4 | | -4+3x=-8(5+4x)+1 | | 5-7(k-5)=96 | | -2y+x=4 | | 4(p)+8(8-p)=44 | | -2y+9=21 | | 5([6-5x])=15x-35 | | a+(a+1)+(a+2)=36 | | 4x+1(x+2)=56-2x | | 2(4+2a)+10=a | | cx^2+3x+c-2=0forx | | -101=5(-7+2m)-6 | | -2/3x+4=3/5x-2 | | 6a+2b=b | | 2-6x=1-x | | x^3+6x^2+x-14=0 | | h/2=-2 | | 68.707+(-99.999)+32.592= | | w^2+5w-594=0 | | 15y-10+k=(ky-1)-y | | -5(-6n-8)-8n=150 | | 2(-8+v)=-16+6v | | 6-5x=20x-35 | | -3+y=25 | | cx^2+3x+c-2=0 |